2021
DOI: 10.1097/gox.0000000000003636
|View full text |Cite
|
Sign up to set email alerts
|

The Objective Effect of Breast Implant Removal and Capsulectomy on Pulmonary Function

Abstract: Background: Breast Implant Illness after aesthetic breast augmentation remains a poorly-defined syndrome. Prior published studies have identified difficulty breathing as a symptom, but definitive improvement in breathing following breast implant removal remains understudied. We hypothesized that patients presenting with breathing symptoms attributed to breast implants would have objective improvement in pulmonary function tests after complete implant/capsule explantation. Methods: A retrospective study of all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…A 2020 study by Kappel and Pruijn also found a significant reduction of symptoms in their patient group after explantation. Another study by Wee et al found that patients presenting with symptomatic SBIs with pulmonary symptoms had significant improvement in pulmonary function after complete implant and capsule explantation.…”
Section: Discussionmentioning
confidence: 97%
“…A 2020 study by Kappel and Pruijn also found a significant reduction of symptoms in their patient group after explantation. Another study by Wee et al found that patients presenting with symptomatic SBIs with pulmonary symptoms had significant improvement in pulmonary function after complete implant and capsule explantation.…”
Section: Discussionmentioning
confidence: 97%
“…In many patients who have complaints about their breast implants, removal (explanting) of the SBI leads to a considerable decline in complaints in a lot of patients, a strong indicator of a causative relation ( 17 , 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The authors state that they always perform a total capsulectomy. 1,2 It is often impossible to remove a thin subpectoral capsule that is tightly adherent to the ribs and extends into the axilla. Attempts to do so might be dangerous.…”
mentioning
confidence: 99%